LEXICAL COMPONENT OF THE SECOND CONSTITUENT OF MODAL VERB CONSTRUCTIONS IN THE TEXTS OF SCIENTIFIC-TECHNICAL COMMUNICATION - Tsinova, M.V. (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 1970)
The paper describes the verbs as second constituents of the modal constructions “modal verb / verbs to have, to be in modal meaning + passive infinitive”, “modal verb / verbs to have, to be in modal meaning + active infinitive” that function in the text corpuses of scientific-technical communication sublanguages “Automotive”, “Heat engineering” and “Electrical engineering” and dependence of their lexical and grammatical peculiarities upon quantitative values.